2011
DOI: 10.1007/s00425-011-1416-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on tolerance of Medicago truncatula and Medicago falcata to freezing

Abstract: Medicago falcata is a legume species that exhibits great capacity of tolerance to abiotic stresses. To elucidate the mechanism underlying tolerance of M. falcata to freezing, we compared the characteristics of M. falcata in response to cold acclimation and freezing with those of the legume model plant Medicago truncatula. M. falcata seedlings were more tolerant to freezing than M. truncatula, as evidenced by a lower value of EL(50) (temperature at which 50% electrolyte leakage after freezing) and greater survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
101
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 56 publications
4
101
0
1
Order By: Relevance
“…MtCAS15 (Medtr7g086340) is induced by low temperature in Medicago spp., and a positive correlation between freezing tolerance and its expression level was identified in Medicago spp. (Monroy et al, 1993a;Pennycooke et al, 2008;Zhang et al, 2011). In addition, MtLTI65 (AC235674_16) and MtY3G1 (Medtr2g014050; a late embryogenesis abundant protein) also were reported to participate in cold stress in previous studies (Nordin et al, 1993;Hincha and Thalhammer, 2012).…”
Section: Mtcbf4 Regulates Genes Linked To Stresses and Developmentmentioning
confidence: 92%
See 3 more Smart Citations
“…MtCAS15 (Medtr7g086340) is induced by low temperature in Medicago spp., and a positive correlation between freezing tolerance and its expression level was identified in Medicago spp. (Monroy et al, 1993a;Pennycooke et al, 2008;Zhang et al, 2011). In addition, MtLTI65 (AC235674_16) and MtY3G1 (Medtr2g014050; a late embryogenesis abundant protein) also were reported to participate in cold stress in previous studies (Nordin et al, 1993;Hincha and Thalhammer, 2012).…”
Section: Mtcbf4 Regulates Genes Linked To Stresses and Developmentmentioning
confidence: 92%
“…Pennycooke et al (2008) reported that Medicago truncatula does not cold acclimate. However, Zhang et al (2011) demonstrated that M. truncatula is able to increase its freezing tolerance after being subjected to cold-acclimating conditions. The different experimental conditions and methods used in these two studies may partly explain the different results (Pennycooke et al, 2008;Zhang et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…falcata, a model candidate for studying abiotic stressresponsive mechanisms in legumes, grows in adverse environments (Zhang et al, 2011). PI502449, a diploid variety of M. falcata, is more tolerant to drought and cold stresses than the model legume Medicago truncatula (Miao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%